Comparative study of three solid oxidants as substitutes of H2O2 used in Fe (III)-oxalate complex mediated Fenton system for photocatalytic elimination of reactive azo dye. (10th March 2018) - Zhang, Congcan; Dong, Yongchun; Li, Bing; Li, Fu
Abstract: Degradation of an azo dye, Reactive Red 195 was conducted with four oxidants including H2 O2, sodium percarbonate (SPC), sodium perborate (SPB) and sodium persulfate (SPS) in the presence of Fe (III)-oxalate complex under light irradiation to investigate the feasibility of three solid oxidants as substitutes of H2 O2 for building a novel solar light-driven Fenton system with the advantages of high stability, cost efficiency and environmental care. Some important effecting factors such as initial concentrations of Fe (III) ion, oxalate ion and oxidant, temperature and light irradiation were also examined and optimized with respect to dye degradation efficiency. The results indicates that dye could be completely degraded using each solid oxidant in place of H2 O2 over 30 min with Fe (III)-oxalate complex under visible irradiation. SPC showed higher oxidizing performance compared with the other two solid oxidants, especially at higher temperature or in the presence of inorganic salt. Hydroxyl radicals ( OH) was identified as the predominant reactive oxygen species for three solid oxidants, especially SPC. Sulfate radicals ( SO4 − ) were found for SPS system. However, it has a less contribution to dye degradation than OH. Besides, superoxide radicals (O2 − ) also participated in dye degradation in all investigated systems. Graphical abstract: Highlights: Dye was degraded using solid oxidant in place of H2 O2 with Fe (III)-OA complex. SPC showed higher oxidizing performance than SPB and SPS. The main mechanism of dye degradation was . OH oxidation. A novel photo-Fenton system with high stability and cost efficiency was developed.